MOISTURE TRANSFER ANALYSIS DURING DRYING OF BRICK BY TEMPERATURE AND RELATIVE HUMIDITY PROFILES - Enrique Martines-Lopez; Leonel Lira-Cortes (European Scientific Journal, ESJ, 2013)
Moisture transfer during drying of bricks is analyzed by temperature and relative humidity profiles which are associated with the drying rate periods. The behavior of moisture profiles and the moment at which the critical moisture content appears is described.Temperature and relative humidity inside of a brick were measured with a differential thermocouple and a capacitive hygrometer respectively; a convection oven was used for the drying.To obtain the corresponding moisture profiles, temperature and mass were measured simultaneously at specific periods of time, until constant mass was achieved.Obtained results show that temperature and relative humidity profiles are useful to describe the moisture transfer during drying; also, could be used for monitoring the behavior of moisture until the equilibrium between the moisture of material and relative humidity of drying media is reached. The analysis was made from ambient temperature up to 200 °C and in was found that critical moisture content of samples of brick by the measurement of the moisture profiles.Finally, the moisture profiles were analyzed in the falling rate period (second falling rate period), and the moisture residuals due to the drying at several temperature values were evaluated.